Litter quality and decomposition in a CO2-enriched Mediterranean forest ecosystem - Angelis, Paolo De (Plant and Soil, 2000)
Six large open top chambers were installed to test the effect of atmospheric [CO2] enrichment on clumps of natural Mediterranean vegetation starting from early spring 1992. To study the impact of [CO2] enrichment on litter decomposition, leaves of three woody species (Quercus ilex L., Phillyrea angustifolia L. and Pistacia lentiscus L.) were collected from the forest ﬂoor and subsequently incubated in situ over a two-year period. The initial slope of the exponential function, describing mass loss, indicated that there was a small negative effect of elevated [CO2] on the decomposition rate of all the species. All regressions were signiﬁcant. The decrease of decomposition rate is particularly notable during the initial stages of decomposition, when the differences of quality parameters, lignin/N and C/N were larger. This study points out that a decrease of decomposition rate may occur under elevated [CO2] conditions; if this effect is coupled to an increase of primary production, there will be a net rise of C-storage in the soils of forest ecosystems. Forest soils may, therefore, represent a potentially increasing sink for this excess carbon.
Keywords: decomposition rates; elevated [CO2]; litter quality; mediterranean forest; Quercus ilex

Litter quality and decomposition in a CO2-enriched Mediterranean forest ecosystem - Angelis, Paolo De (Plant and Soil, 2000)
Six large open top chambers were installed to test the effect of atmospheric [CO2] enrichment on clumps of natural Mediterranean vegetation starting from early spring 1992. To study the impact of [CO2] enrichment on litter decomposition, leaves of three woody species (Quercus ilex L., Phillyrea angustifolia L. and Pistacia lentiscus L.) were collected from the forest ﬂoor and subsequently incubated in situ over a two-year period. The initial slope of the exponential function, describing mass loss, indicated that there was a small negative effect of elevated [CO2] on the decomposition rate of all the species. All regressions were signiﬁcant. The decrease of decomposition rate is particularly notable during the initial stages of decomposition, when the differences of quality parameters, lignin/N and C/N were larger. This study points out that a decrease of decomposition rate may occur under elevated [CO2] conditions; if this effect is coupled to an increase of primary production, there will be a net rise of C-storage in the soils of forest ecosystems. Forest soils may, therefore, represent a potentially increasing sink for this excess carbon.
Keywords: decomposition rates; elevated [CO2]; litter quality; mediterranean forest; Quercus ilex